2018
DOI: 10.1007/s13205-018-1270-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis of Bacillus velezensis reveals a potential for degrading lignocellulosic biomass

Abstract: Genomes of 24 sequenced strains were characterized to identity shared and unique genes of lignocellulolytic enzymes and predict potential to degrade lignocellulose. All 24 strains had genes that encoded lignocellulolytic enzymes, with potential to degrade cellulose and hemicelluloses. Several lignocellulosic genes related to cellulose degradation were universally present, including one GH5 (endo-1,4-β-glucanase), one GH30 (glucan endo-1,6-β-glucosidase), two GH4 (6-phospho-β-glucosidase, 6-phospho-α-glucosidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
(35 reference statements)
0
24
0
3
Order By: Relevance
“…While B. velezensis SMR produced NC, interestingly, different B. velezensis isolates were shown to possess the genes encoding putative lignocellulolytic enzymes and were able to efficiently degrade lignocellulosic, cellulosic and hemicellulosic materials 25 , 26 . Moreover, it has been shown that B. velezensis strain 157 is able to degrade various agro-industrial byproducts including soybean meal, wheat bran, sugarcane bagasse, wheat straw, rice husk, maize flour and maize straw utilized in biofuel production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While B. velezensis SMR produced NC, interestingly, different B. velezensis isolates were shown to possess the genes encoding putative lignocellulolytic enzymes and were able to efficiently degrade lignocellulosic, cellulosic and hemicellulosic materials 25 , 26 . Moreover, it has been shown that B. velezensis strain 157 is able to degrade various agro-industrial byproducts including soybean meal, wheat bran, sugarcane bagasse, wheat straw, rice husk, maize flour and maize straw utilized in biofuel production.…”
Section: Resultsmentioning
confidence: 99%
“…Percentage of bacterial isolates forming thin mesh layer on HS broth after static growth for 7 days at 30 °C and showing positive results with Fehling test. and hemicellulosic materials 25,26 . Moreover, it has been shown that B. velezensis strain 157 is able to degrade various agro-industrial byproducts including soybean meal, wheat bran, sugarcane bagasse, wheat straw, rice husk, maize flour and maize straw utilized in biofuel production.…”
mentioning
confidence: 99%
“…It, however, contained putative gene clusters encoding sporulation, biofilm formation, and antibiotic synthesis, (macrolactin, bacilysin, bacillibactin, surfactin, bacillopeptin, bacillaene, iturin, fengycin, and difficidin) that could also be found in these strains (Pandin et al, ) (Tables and ). Gene clusters for amylocyclicin (detected in B. velezensis FZB42 and B. velezensis LS69) (Liu et al, ; Scholz et al, ), butirosin (detected in B. velezensis LM2303) (Chen, ), ericin (detected in B. velezensis RC 218) (Palazzini et al, ), and lignin degradation (Chen et al, ) were located in NWUMFkBS10.5 genome.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 5 and Figure 7a, Figure S5h) of NWUMFkBS10.5, even though the NWUMFkBS10.5 blast did not branch directly with any of the iturin operons (Supporting Information Figure S6). It, however, contained putative gene clusters encoding sporulation, biofilm formation, and antibiotic synthesis, (macrolactin, bacilysin, bacillibactin, surfactin, bacillopeptin, bacillaene, iturin, fengycin, and difficidin) that could also be found in these strains (Pandin et al, 2018) Huang, Guo, and Yousef (2014), (detected in B. velezensis RC 218) (Palazzini et al, 2016), and lignin degradation (Chen et al, 2018) were located in NWUMFkBS10.5 genome.…”
Section: Production Of Biosurfactants Has Been Reported For Manymentioning
confidence: 99%
“…Recent comparative genome analyses among various B. velezensis spp. have revealed their potential as degraders of lignocellulosic biomass [24]. An open reading frame encoding a novel AFase (BvAF) was found from the genome of B. velezensis FZB42 [25].…”
Section: Gene Cloning and Expression Of Bvafmentioning
confidence: 99%